Farmers Knowledge, Practices and Health Problems Associated with Pesticides Use in West Tripoli, Libya - , Hamza S. Abdalla Lagili; , Hesham Ayouz; , Serife Gunduz; , Ndifreke Etuk Williams; , Olusola Bamisile; , Onyinyechi Jas Kamalu (Archives of Current Research International, 2020)
Aims: This study focuses on farmers’ knowledge, practices and health problems associated with pesticide use in west Tripoli, Libya. Study Design: This study concentrated on the farmer being above 18 years, a permanent resident in the study area and the respondent’s willingness obliged to the study protocols and complete the study. Place and Duration of Study: The study is a cross-sectional one among 300 farmers in the West Tripoli district of the Libya which concentrated on the adult population conducted in 2017. Methodology: The associations between pesticide-handling practices, knowledge and attitude and factors potentially influencing them were explored by means of t-test, ANOVA and descriptive statistics using the statistical software SPSS 20.0. The reliability of the construct was examined using Cronbach’s alpha which was not below 0.700 indicating excellent internal consistency. Results: Farmers re-spray the crops with surplus pesticide mixture. They throw away surplus pesticide mixture on uncultivated land wash and reuse emptied pesticide containers to store water. Knowledge associated with pesticide use and practices associated with it was also not statistically significant related to attitudes towards educational level. Awareness of pesticide use and handling and therefore showed that there was no statistically significant difference between a male and female farmers’ awareness of pesticide use and handling. There is no significant relationship between farmer’s monthly income and knowledge regarding pesticide use and there was linear relationship practices with respect to pesticides used and symptoms experienced after exposure to pesticides. Level of education affect farmer’s knowledge and practices associated with pesticide use and the ANOVA, F = 1.489 and p =.000 (> 0.05) suggests that the test was not statistically significant, on how gender affect the awareness of pesticide use and handling the result showed that there was no statistically significant difference (t (298) = -.460, p = .664 > 0.05) between male and female farmers’ awareness of pesticide use and handling. Therefore, male and female gender do not affect the awareness of pesticide use and handling. Conclusion: The results of farmers practices regarding the use of protective measures and hygiene practices with the potential for exposure to pesticides indicates that farmers use gloves, face mask, respirator and boots. Moreover, the farmers keep their working clothe at home and the spraying methods used are knapsack, hand- held can, and tractor and can be concluded that the danger of exposure increase when farmers disregard safety directives on the correct utilization of pesticides, PPE utilization and using sanitary practices.